Silane Deuteration Catalyzed by Ruthenium Bis(dihydrogen) Complexes or Simple Metal Salts. Issue 4 (20th February 2014) - Smart, Katharine A.; Mothes‐Martin, Emmanuelle; Annaka, Tatsuro; Grellier, Mary; Sabo‐Etienne, Sylviane
Abstract The deuteration of a diverse group of silanes: alkyl‐, aryl‐, alkoxy‐ and chlorosilanes, siloxane and silazane, under an atmosphere of dideuterium (D2) was explored with ruthenium bis(dihydrogen) dihydride complexes and hydrated metal salts. Deuterium incorporation of greater than 97% for the silanes O(SiMe2H)2, Et3SiH, (EtO)3SiH and Me2ClSiH was possible with 0.1 mol% of the ruthenium complex [RuH2(η2‐H2)2(PCyp3)2] [0.05 mol% for O(SiMe2H)2] when catalysis was conducted in the neat silane at 30 °C under 1 bar of D2 for 3.5 h. The air‐stable ruthenium trichloride salt RuCl3⋅x H2O was also an efficient catalyst for the deuteration of O(SiMe2H)2 and Et3SiH; deuterium incorporations for the two silanes of 93% and 90%, respectively, were possible under the same conditions as for [RuH2(η2‐H2)2(PCyp3)2] with 0.1% catalyst loading. Hydrogen–deuterium exchange of O(SiMe2H)2 catalyzed by the rhodium trichloride (RhCl3⋅x H2O) and iridium trichloride (IrCl3⋅x H2O) was similarly efficient as with RuCl3⋅x H2O although catalytic alacrity dropped for Et3SiH. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>